2013
DOI: 10.5032/jae.2013.04162
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Technical Expression of Academic Knowledge: The Science-in-CTE Pilot Study

Abstract: The Science-in-CTE pilot study tested a curriculum integration model that enhanced the science that occurs in CTE curricula. The study replicated the National Research Center for Career and Technical Education's (NRCCTE) Math-in-CTE experimental research design (Stone, Alfeld, & Pearson, 2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…al., 2015;Roberts & Ball, 2009). The content taught in CTE courses is a result of what the workforce needs, which explains why CTE teachers continue to make their courses hands-on and applicable to the real world (Pearson, Young, & Richardson, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…al., 2015;Roberts & Ball, 2009). The content taught in CTE courses is a result of what the workforce needs, which explains why CTE teachers continue to make their courses hands-on and applicable to the real world (Pearson, Young, & Richardson, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Career and technical education (CTE) is driven by the needs of the workforce (Pearson, Young, & Richardson, 2013) and has been around for more than a century (Wilkin & Nwoke, 2011). Within an agricultural education program, CTE relies on educators to keep a close connection with the industries in which they work (Pearson, Young, & Richardson, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"The purpose of CTE is to develop the knowledge and skills required for successful employment in a given industry" (Roberts & Ball, 2009 p. 82). CTE is driven by the needs of the workplace (Pearson, Young, & Richardson, 2013), and in Iowa, CTE includes organized educational programs that offer a sequence of courses, which are directly related to the preparation of individuals for employment regarding current or emerging occupations ("Career and Technical Education," 2017). These programs continue to adapt and evolve as workforce demands adjust (Pearson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that models integrating STEM concepts into CTE courses were viable, and noted "STEM-focused education can be incorporated into any CTE delivery system, program, or curricular or pedagogical approach within CTE" (Stone, 2011, p. 13). Both the Math-in-CTE initiative (Stone, Alfeld, & Pearson, 2008) and the Science-in-CTE initiative (Pearson, 2015;Pearson, Young, & Richardson, 2013) have been conducted to examine the successful learning of STEM concepts in CTE courses. These programs have yielded positive results and longitudinal studies are underway.…”
Section: Review Of Literaturementioning
confidence: 99%